The Suitability of Bailey Method for Design of Local Asphalt Concrete Mixture - Ahmed Fahim Rahi; Amjad Albayati (Salehan Institute of Higher Education, 2021)
The study investigated the behaviour of asphalt concrete mixes for aggregate gradations, according to the Iraqi specification using the Bailey method designed by an Excel spreadsheet. In mixing aggregates with varying gradations (coarse and fine aggregate), The Bailey method is a systematic methodology that offers aggregate interlocking as the backbone of the framework and a controlled gradation to complete the blends. Six types of gradation are used according to the bailey method considered in this study. Two-course prepared Asphalt Concrete Wearing and Asphalt Concrete binder, the Nominal Maximum Aggregate Sizes (NMAS) of the mixtures are 19 and 12.5 mm, respectively. The total number of specimens was 240 for both layers (15 samples) for each Chosen Unit Weight (CUW). The Marshall Test results show the increase in stability and decrease in flow and bulk density when the rise in CUW for both courses. In volumetric properties, VMA increases when the increase in CUW. When an increase in CUW air void increases gradually. The permanent deformation for the coarse aggregate (95, 100, 105% CUW) has more resistances than the fine aggregate (80, 85, 90%) wearing and binder coarse. The CUW (105%) blend of wearing, and binder course has a high value of stability and resistance to permanent deformation (11.9, 11.1 kN). The CUW above mentioned is considered a good design aggregate structure and produces improvement to the Marshall properties, leading to better performance for pavement roads and higher resistance to distresses. Doi: 10.28991/cej-2021-03091693 Full Text: PDF